Clostridium septicum Sepsis and Colon Carcinoma: Report of 4 Cases. (26th June 2011) - Mao, Eric; Clements, Aine; Feller, Edward
Abstract : An association exists between colon carcinoma and Clostridium septicum infection, especially bacteremia. We reviewed retrospectively all positive blood cultures for this organism at a 300-bed general hospital over 4 years. Four of 15 cases were associated with concurrent colon carcinoma. C. septicum infection was the presenting feature of previously undiagnosed large bowel malignancy in three patients. We report this small case series to alert clinicians to the diverse spectrum and diagnostic difficulties of this rare, potentially catastrophic association. Although commonly associated with necrotizing skin or soft tissue infections, this bacterium can present with nonspecific or atypical symptoms. All patients with positive blood cultures for C. septicum, even without clinical suspicion of large bowel malignancy, should undergo colonoscopy to evaluate for colon carcinoma.